Drought stimulates root exudation of organic nitrogen in cotton (Gossypium hirsutem) - Coker, Harrison R.; Lin, Heng-An; Shackelford, Caleb E. B.; Tfaily, Malak M.; Smith, A. Peyton; Howe, Julie A. (Frontiers in Plant Science, 2024)
Root exudation of N is a plant input to the soil environment and may be differentially regulated by the plant during drought. Organic N released by root systems has important implications in rhizosphere biogeochemical cycling considering the intimate coupling of C and N dynamics by microbial communities. Besides amino acids, diverse molecules exuded by root systems constitute a significant fraction of root exudate organic N but have yet to receive a metabolomic and quantitative investigation during drought. To observe root exudation of N during drought, mature cotton plants received progressive drought and recovery treatments in an aeroponic system throughout their reproductive stage and were compared to control plants receiving full irrigation. Root exudates were nondestructively sampled from the same plants at 9 timepoints over 1821 days. Total organic C and N were quantified by combustion, inorganic N with spectrophotometric methods, free amino acids by liquid chromatography-mass spectroscopyhigh performance liquid chromatography (LCMSHPLC), and untargeted metabolomics by Fouriertransform ion cyclotron resonance-mass spectrometry (FT-ICR-MS). Results indicate that organic N molecules in root exudates were by far the greatest component of root exudate total N, which accounted for 20-30% of root exudate mass. Drought increased root exudation of organic N (62%), organic C (6%), and free amino acid-N (562%), yet free amino acids were < 5% of the N balance. Drought stress significantly increased root exudation of serine, aspartic acid, asparagine, glutamic acid, tryptophan, glutamine, phenylalanine, and lysine compared to the control. There was a total of 3,985 molecules detected across root exudate samples, of which 41% contained N in their molecular formula. There were additionally 349 N-containing molecules unique to drought treatment and 172 unique to control. Drought increased the relative abundance and redistributed the molecular weights of low molecular weight N-containing molecules. Time-series analysis revealed root exudation of organic N was stimulated by drought and was sensitive to the degree of drought stress.